Bovine cysticercosis in feedlot cattle in central region of Iran - Gholami, Naser (J Parasit Dis, 2019)
The cestode, Taenia saginata is a zoonotic tapeworm that it’s larval stage which known as Cysticercus bovis cause cyst formation in cattle’s organs such as heart, lung, liver, tongue, esophagus and diaphragm muscle, despite the infected cattle may show no clinical signs. Antemortem diagnosis of bovine cysticercosis can be made by antigen detecting ELISA. In a feedlot near city of Arak, beef cattle had different degrees of lethargy, dullness, unthriftiness and were reluctant to move. In postmortem examination of cattle, samples were collected from heart tissue and stained by H&E method for light microscopic examination. 10 ml of blood samples were taken from jugular veins of 90 cattle that were going to be sent to slaughterhouse. Serums obtained from blood samples were investigated for presence of C. bovis antigen by ELISA assay. Soils and dusts from farm yard, pen’s floor, feed store and both toilets of workers and employer were sampled and evaluated for presence of parasite eggs by floating method. Cysticercus bovis antigen were identified in serums of 18 cattle; and also, samples from workers toilet was contaminated by eggs of T. saginata. This study showed that serologic methods in conjunction with meat inspection can be used for diagnosis of bovine cysticercosis. The aim of this study is to identify infected cattle with C. bovis by serologic methods before slaughter and determine microscopic characteristics of lesions on postmortem examination in central area of Iran.